БЕТУЛИННИНГ НАЗАРИЙ ВА ЭКСПЕРИМЕНТАЛ ГЕОМЕТРИК ХАРАКТЕРИСТИКАЛАРИНИ ТАҚҚОСЛАШ (Scientific journal of the Fergana State University, 2023)
The study of betulin and its derivatives is of great importance, since the programs of mathematical modeling enable a qualitative study of the relationship between structure-spectrum-properties. As a result of the theoretical search, it is possible to determine still non-synthesized highly-biologically active derivatives of betulin.